Pengaruh Corporate Governance Terhadap Kinerja Unit Usaha Syariah Perbankan Indonesia: Pendekatan Maqashid Syariah Index - Cahyo Putri, Raden Roro Nurul Aini (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to provide empirical evidence regarding the performance of maqashid sharia on Sharia Business Units (UUS) in Indonesia during 2016-2020. The study employed purposive sampling in order to gather secondary data from yearly financial reports released by Indonesia's Islamic Commercial Banks and financial reports issued by the Financial Services Authority (OJK). The methods used are descriptive statistical techniques and quantitative descriptive techniques using the Maqashid-based Performance Evaluation Model (MPEM) approach. With an average score of 8253.08, the study's findings show that Maybank Bank is the US financial institution that ranks highest among US banks for operating in compliance with Maqashid Syariah over the 2016–2020 timeframe. Next with a score difference of 116.22 is UUS Bank Sinarmas. Finally, with an average value of 3884.84, making UUS Bank CIMB Niaga as the UUS with the smallest maqashid index performance. Furthermore, DPS characteristics and board structure play a significant part in enhancing UUS performance. Additionally, this study discovered that, in contrast to the size of the board of commissioners, which has an adverse effect on maqashid syariah performance, DPS with DPS Size, DPS cross-membership, DPS educational qualifications, and DPS Reputation had a favorable influence on Maqashid Syariah performance. .